Cyclohexane extract of walnut leaves improves indices of oxidative stress, total homocysteine and lipids profiles in streptozotocin‐induced diabetic rats - Jelodar, Gholamali (Physiol Rep, 2020)
This study aimed to evaluate the effect of two doses of cyclohexane extract of walnut leaves on total homocysteine, lipids profiles, and indices of oxidative stress including superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT), and malondialdehyde (MDA) in diabetic rats. Diabetes was induced by a single intraperitoneal (IP) injection of streptozotocin (50 mg/kg BW). Twenty‐eight male Sprague Dawley rats were randomly divided into four groups, group I: control (received sesame oil as vehicle), group II: diabetic control (received sesame oil), group III and IV: diabetic rats treated by 150 and 250 mg/kg body weight (BW) per day extract of walnut leaves, respectively. All groups were treated for 28 days via oral gavage. Fasting blood glucose (FBG) level and body weight measured before injection, 3 days after injection, and on days 0, 7, 14, 21, and 28 of treatment. At the end the 28th day of the experiment, blood samples collected via heart puncture and the sera were used for estimation of the above‐mentioned parameters. The results showed a decrease in FBS, TC, TG, LDL‐c, VLDL‐c, homocysteine, and MDA level and increase in the level of HDL‐c in diabetics treated by walnut leave extracts in a dose‐dependent manner after 28 days. The activity of antioxidant enzymes significantly increased in treated groups compared with diabetic control. It can be concluded that cyclohexane extract of walnut leaves has an overall beneficial effect on body weight, fasting blood glucose, lipids profile, antioxidant enzyme activities, and homocysteine.